PENGARUH GOOD CORPORATE GOVERNANCE (GCG) MAKRO EKONOMI SIZE TERHADAP INVESTMENT DECISION DAN VALUE OF THE FIRM DENGAN PROFITABILITAS SEBAGAI VARIBEL INTERVENING SERTA FINANCING DECISION SEBAGAI VARIABLE MODERATING (Studi Pada Perusahaan Jasan Konstruksi BUMN Yang Listed Di PT Bursa Efek Indonesia) - Sugiarto, Sugiarto (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2019)
The purpose of this study is to analyze variables that related to investment decisions and corporate values of companies which listed at Bursa Efek Indonesia. Samples of this research are; (1) PT. Adhi Karya (Persero) Tbk, (2) PT. Pembangunan Perumahan (Persero) Tbk, (3) PT. Waskita Karya (Persero) Tbk, (4) PT. Wijaya Karya (Persero) Tbk, selected by purposive sampling. Analysis of this research using Partial Least Square (PLS). The results show that the effect Good Corporate Governance (GCG) on profitability, investment decision and value of the firm is significant, Macro Economy to profitability is not significant, Macro Economy to investment decision and value of the firm is significant, Size to profitability and value of the firm is significant, Size to investment decision is not significant. Profitability to investment decision and value of the firm is significant. Investment decision to value of the firm is significant. Financial decision as a moderator variable on profitability linkage to investment decision is not significant. Financial decision as a moderator variable on profitability linkage to the value of the firm is significant. Financial decision on investment decision and value of the firm is significant.